2023
DOI: 10.1002/chem.202303770
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Applications of Thioamides and Methods for Their Synthesis

Tobias N. Hansen,
Christian A. Olsen

Abstract: Thioamides are naturally occurring isosteres of amide bonds in which the chalcogen atom of the carbonyl is changed from oxygen to sulfur. This substitution gives rise to altered nucleophilicity and hydrogen bonding properties with importance for both chemical reactivity and non‐covalent interactions. As such, thioamides have been introduced into biologically active compounds to achieve improved target affinity and/or stability towards hydrolytic enzymes but have also been applied as probes of protein and pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 156 publications
(191 reference statements)
0
0
0
Order By: Relevance
“…22,23 Various research studies have demonstrated the potential of compounds containing thioamide-based ligands for various biological applications, particularly their antibacterial properties. 24,25 At the same time, medicinal chemists have used thioamides to improve the pharmacokinetic properties and the thermal and proteolytic stability of compounds containing amide moieties. 24 Pharmaceutical compounds containing the thioamide group, such as drugs for hyperthyroidism (methimazole, methyl-, and propylthiouracil), have been found to react with iodine molecules during a multistep and complex process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Various research studies have demonstrated the potential of compounds containing thioamide-based ligands for various biological applications, particularly their antibacterial properties. 24,25 At the same time, medicinal chemists have used thioamides to improve the pharmacokinetic properties and the thermal and proteolytic stability of compounds containing amide moieties. 24 Pharmaceutical compounds containing the thioamide group, such as drugs for hyperthyroidism (methimazole, methyl-, and propylthiouracil), have been found to react with iodine molecules during a multistep and complex process.…”
Section: Introductionmentioning
confidence: 99%
“…Organic ligands such as thioamides were deemed synthetic isostere for amides in protein scaffolds and peptides before they were discovered in natural molecules . The strategic incorporation of thioamide into both synthetic and natural compounds has the potential to enable both dramatic and subtle changes in amide interactions due to this single-atom substitution. , Various research studies have demonstrated the potential of compounds containing thioamide-based ligands for various biological applications, particularly their antibacterial properties. , At the same time, medicinal chemists have used thioamides to improve the pharmacokinetic properties and the thermal and proteolytic stability of compounds containing amide moieties . Pharmaceutical compounds containing the thioamide group, such as drugs for hyperthyroidism (methimazole, methyl-, and propylthiouracil), have been found to react with iodine molecules during a multistep and complex process .…”
Section: Introductionmentioning
confidence: 99%